1999
DOI: 10.1177/108835769901400405
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Multimethod, Multilevel Literacy Program for Students with Mental Retardation

Abstract: The present descriptive study was a year-long investigation into the literacy development of nine elementary students with mild to moderate mental retardation (mean CA = 9.8; IQ scores available for seven students, mean IQ = 57.7; IQ range = 40-76). The teacher instructed the students using a balanced, multimethod, multilevel language arts framework that blended more traditional approaches to teaching reading, such as phonics and basal instruction, with holistic and contextualized approaches that included read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…The results indicated that children who received the phonological reading instruction performed better on tests of “sounding out” (i.e., speaking the individual phonemes in a printed word) and pronouncing a whole word compared to the control group for a set of instructed items and a set of transfer items. A study by Hedrick, Katims, and Carr (1999) obtained similar results. They implemented a multifaceted reading intervention with nine children with mild to moderate intellectual disabilities.…”
Section: Phonological Awareness and Readingsupporting
confidence: 64%
See 1 more Smart Citation
“…The results indicated that children who received the phonological reading instruction performed better on tests of “sounding out” (i.e., speaking the individual phonemes in a printed word) and pronouncing a whole word compared to the control group for a set of instructed items and a set of transfer items. A study by Hedrick, Katims, and Carr (1999) obtained similar results. They implemented a multifaceted reading intervention with nine children with mild to moderate intellectual disabilities.…”
Section: Phonological Awareness and Readingsupporting
confidence: 64%
“…For example, Hedrick and colleagues (1999) demonstrated that a multimethod approach to literacy instruction that emphasized decoding, comprehension, vocabulary, and writing resulted in significant reading gains for individuals with mild to moderate intellectual disability . Likewise, Conners and colleagues (2006) demonstrated that a phonological skills instruction program helps children with intellectual disability learn skills related to phonological awareness.…”
Section: Discussionmentioning
confidence: 99%
“…All activities undertaken in the training sessions focused on the use of literacy teaching models and strategies based around the theme of developing life stories with adults with intellectual disabilities (Hedrick et al 1999, Guthrie and Davis 2003, Salinger 2003, Sigafoos and Arthur 2005. The first authors developed video clips of young adults with intellectual disabilities working with tutors.…”
Section: Training Sessionsmentioning
confidence: 99%
“…However, adolescent and adult learning, especially literacy learning, is not often considered an option for individuals with moderate and higher support needs due to their intellectual disability (van Kraayenoord, Moni, Jobling, & Ziebarth, 2002). In secondary school and as part of their post-school options programs, the focus is often on social, vocational, and daily living skills to the exclusion of meaningful literacy (Hedrick, Katims, & Carr, 1999).…”
Section: Introductionmentioning
confidence: 98%